Meningkatkan Hasil Belajar dengan Metode Contextual Teaching Learning pada Mata Pelajaran Sejarah - Pasaribu, Esmeria (Universitas Negeri Medan, 2015)
This researchâs subject is 36 person of students at class of Social Science-3 grade XII, as the researchâs object is the method of Contextual Teaching Learning.Â The instrument of collecting data are the questionaire and the students score list . Based on pre test result to the 36 students, shows that 28 who obtained low score predicated ânot passedâ as had not yet achieved Minimal Passing Score of 70, while the rest of 8 passed by obtaining the passing score. In the first cycle, there were 16 of student passed by obtaining the passing score of 70, whereas the rest of 20 were not passed by did not obtaining the passing score. In the second cycle there were 34 of students passed the test while the rest of 2 students were not passed the test. By based on several results of pre test, post test of the first cycle, and post test of the second cycle, indicated increasing the result of teaching-learning significantly. Therefore, could be concluded that using the method of Contextual Teaching Learning can be increase achievement of student learning at the subject of history on the subject matter of Analising Development of World History and Position of Indonesia in the middle of International Politic and Eco-nomic Changing post Second World War.